HRM Perceptions And Organizational Citizenship Behavior: A Moderated And Mediation Model Of Innovative Work Behavior And Hierarchical Position - Yuningsih, Yuningsih; Nova Mardiana; Muhammad Derry, Prasetya (ICSIGER- International Conference on Science and Emerging Technology, 2025)
This study examines the influence of employees’ perceptions of Human Resource Management (HRM) practices on Organizational Citizenship Behavior (OCB), with Innovative Work Behavior (IWB) as a mediator and hierarchical position as a moderator, within the Indonesian banking sector undergoing digital transformation. A quantitative explanatory design was employed using survey data from 843 employees across top, middle, and lower managerial levels. The study applied Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the hypothesized relationships. The results reveal that employment security and performance assessment & reward significantly predict OCB, whereas job autonomy, recruitment, and training & development exhibit no direct effects. IWB partially mediates the relationship between HRM practices and OCB, particularly for job autonomy, training & development, and performance assessment & reward. Multi-group analysis further indicates that employment security exerts stronger effects among lower- and middle-level employees, while performance assessment & reward is more salient for top-level employees. The findings extend Social Exchange Theory and the Theory of Purposeful Work Behavior by elucidating the psychological mechanisms linking perceived HRM practices to OCB across hierarchical levels. Practically, the study highlights the need for contextually adaptive HRM strategies to enhance engagement and discretionary behaviors in organizations facing rapid change.